Biogeographical patterns of grasses (Poaceae) indigenous to South Africa, Lesotho and Eswatini. (10th December 2021) - Trytsman, Marike; Muller, Francuois L; Morris, Craig D; van Wyk, Abraham E
Abstract : The ecological and economical importance of African grasses in sustaining animal production prompted studies to quantify the wealth of grass genetic resources indigenous to southern Africa. Plant collection and occurrence data were extracted from two southern African datasets, BODATSA and PHYTOBAS, and analysed to establish biogeographical patterns in the grass flora indigenous to South Africa, Lesotho and Eswatini. A total of 1 648 quarter degree grid cells, representing 674 grass species, were used in an agglomerative hierarchical clustering to determine biogeographical units being referred to as grasschoria. Six distinct groups formed, mainly following existing biome vegetation units, termed the Grassland, Indian Ocean Coastal Belt, Fynbos, Savanna, Central Arid Region and Succulent Karoo grasschoria. The description focuses on associated phytochoria, floristic links, key species, climate and soil properties. The main gradient distinguishing grasschoria was a rainfall-temperature gradient. The collection, conservation and breeding of pasture grass species adapted to especially arid and semi-arid environments, could be managed more efficiently by using these results, but also calling on the need to describe and label infraspecific genetic variants, including ecotypes.